1977
DOI: 10.1128/iai.15.2.594-600.1977
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of pili to colonial morphology among pathogenic and nonpathogenic species of Neisseria

Abstract: Growth in colonies with type 1 morphology and the presence of pili are characteristics that have been associated with virulence of gonococci for humans. To determine whether the presence of pili per se might be responsible for colony type 1 morphology, the relationship ofpili to colony type was examined in various species ofNeisseria. Short pili (175 to 210 nm in length) were seen only on nonpathogenic neisseria, whereas long pili (up to 4,300 nm) were seen on organisms ofboth nonpathogenic and pathogenic spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…These workers also assessed piliation of gonococci in vivo by carbonplatinum-shadowing techniques and found that in purulent exudates the ratio of nonpiliated to piliated gonococci was 18:1 (i.e., 94% of the gonococci lacked pili) and the number of pili per microorganism was low. Thus, piliation of gonococci in vivo differed from the piliation of type 1 or 2 gonococci grown in our own or other laboratories, of which virtually all would have 10 to 30 pili per microorganism (20,26). Evans (10) found no pili upon thin-section electron microscopy of gonococci in specimens from cervical biopsies and concluded that pilii are a laboratory phenomenon confined to growth on artificial media or in organ culture models."…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…These workers also assessed piliation of gonococci in vivo by carbonplatinum-shadowing techniques and found that in purulent exudates the ratio of nonpiliated to piliated gonococci was 18:1 (i.e., 94% of the gonococci lacked pili) and the number of pili per microorganism was low. Thus, piliation of gonococci in vivo differed from the piliation of type 1 or 2 gonococci grown in our own or other laboratories, of which virtually all would have 10 to 30 pili per microorganism (20,26). Evans (10) found no pili upon thin-section electron microscopy of gonococci in specimens from cervical biopsies and concluded that pilii are a laboratory phenomenon confined to growth on artificial media or in organ culture models."…”
Section: Resultsmentioning
confidence: 74%
“…(pH 7.45). A Formvar-carboncoated grid was inverted and floated successively on the surface of one drop each of the bacterial suspension, 1% glutaraldehyde in 0.1 M cacodylate buffer (pH 7.4), distilled water, and 1% sodium phosphotungstate (pH 6.5) under the conditions previously described (20). The grids were examined with a Phillips 300 electron microscope at 60 kV.…”
Section: Materlu1s and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less is known about meningococcal pili; however, they share morphologic characteristics, antigenicity, and some amino acid sequence homology with gonococcal pili (12,29,32). Pili have also been observed on commensal Neisseria species (24,37), but the function of these pili and their relationship to pili found on pathogenic species are unclear. P.11 is a heat-modifiable outer membrane protein fouhd on gonococci (21,34).…”
mentioning
confidence: 99%
“…Each panel was probed with a different DNA probe. ( were then negatively stained with 1% potassium phosphotungstate E~t 1 ri L (pH 7.0) on carbon-coated Formvar grids as described by McGee et al (24). The specimens were examined with a JEOL 100 CX transmission electron microscope at 80 kV.…”
mentioning
confidence: 99%